(untitled) (BIRDEM Medical Journal, 2020)
Renal impairment is occasionally reported in association with hypothyroidism. We report a case of a middle aged man, who presented with features of rhabdomyolysis and acute kidney injury which was ascribed to underlying undiagnosed hypothyroidism. The etiology is presumed to be multifactorial; hemodynamic effects and a direct effect of thyroid hormone on the kidney play important role. This case enlivens the necessity of assessing thyroid function in cases of unexplained renal failure. Awareness about this rare presentation of a common disease would alert the physician to effectively treat this dreaded yet reversible complication. Birdem Med J 2021; 11(1): 72-74